Application of ground penetrating radar methods in soil studies: A review - Zajícová, Katerina; Chuman, Tomas (Geoderma, 2019)
Applications of ground penetrating radar (GPR) in soil surveys promise cost and time benefits together with the possibility of repeating surveys at the same locations due to the method's non-destructiveness to the ground surface. After its successful application to earth sciences surveying of the deep subsurface, GPR was used in soil surveys; however, its application in soil surveys has been difficult. This paper aims to provide an overview of the application of GPR in soil surveys. This paper focuses on methods to estimate the soil water content by various approaches, such as determining the electromagnetic signal velocity in a soil by analyses of reflections, ground wave or guided wave approaches, and the full-waveform inversion method; to characterize soil and peat stratigraphy, with an emphasis on organic horizons; and to detect tree roots. GPRs have been relatively successfully applied in a wide spectrum of surveys, but under favourable conditions. More complex techniques using numerical modelling that have emerged in recent years might have the potential to be more successful. •GPR can estimate soil moisture with root mean square error of <0.05 cm3/cm3.•GPR can assist to detect soil or peat stratigraphy and estimate layers thicknesses.•Root biomass can be approximated from roots and their diameters detected using GPR.•Measurement approach must be chosen with respect to the purpose and field conditions.